Biogas upgrading by chemical absorption using a packed column apparatus - Abdeen, Fouad R. H.; Mel, Maizirwan; Jami, Mohammed Saedi; Ihsan, Sany Izan; Ismail, Ahmad Faris (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Nowadays, the continuously increasing diminution of conventional fossil fuels has increased the interest of the research and development sectors in finding green and renewable supplements. A momentous attention has been given to the production of biogas via the anaerobic digestion of biomass. Biogas major components are methane, carbon dioxide and traces of hydrogen sulfide, ammonia and nitrogen. Hydrogen sulfide and other impurities are usually removed in a process called biogas purification. Biogas upgrading process is the process by which carbon dioxide (composing 40% of the biogas) is removed. In this study chemical absorption process for upgrading biogas was performed using 3 different solvents (sodium hydroxide, monoethanolamine and ammonia). The three different solvents have shown great ability in absorbing carbon dioxide as well as hydrogen sulfide using a lab scale packed column absorber-apparatus. The lab scale apparatus is designed to manipulate the different process parameters of liquid/gas flow ratio, column height and solvent type. Varying the different process parameters a biogas purity up to 93.3% methane content was obtained.